THE NUANCES OF HUMOR TRANSLATION IN TERRY PRATCHETT'S 'GOOD OMENS' - Gubaydullin, Artur (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2023)
This article explores the complexities of translating humor in Terry Pratchett's renowned novel, 'Good Omens.' The study delves into the challenges faced by translators when attempting to convey the intricacies of humor across different languages and cultures.